Purchasing Car Insurance: What College Students Should Know - Nicholas Horvath; Jorge Ruiz-Menjivar; Sarah M. Ellis (EDIS, 2021)
Florida law requires drivers to have car insurance that provides financial protection in the event of a mishap. This 4-page publication provides an overview of auto insurance requirements in Florida as well as a glossary of car insurance terms for college students. Written by Nicholas Horvath, Jorge Ruiz-Menjivar, and Sarah M. Ellis, and published by the UF/IFAS Department of Family, Youth and Community Sciences, January 2021.